MINAT MAHASISWA MEMBACA (STUDY DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU PEKANBARU) - Afni Mariani Batubara; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Interest in reading is a source of motivation that influence the learning process, thedevelopment of science, and encouraging to observe, to feel interested and excited towardsreading activities that they want to do these activities with a will of its own. The phenomenon ofinterest in reading among students has become a common thing in the lecture. Many studentslack the reading interests. Student is one component of the academic community who arestudying science, and therefore should be read subject the student agenda. By reading will makea source of inspiration, a source of knowledge and hone student criticality. The purpose of theresearch conducted to determine the interest in reading among students Strata 1 (S1) in theFaculty of Social and Political Sciences, University of Riau Pekanbaru with a focus on studentcharacteristics, interests and reasons for students to read, perceived satisfaction in readingactivities in the course. Respondents in this study amounted to 6 students with the characteristicsof S1, a student, has a level of diligent and industrious conduct reading activities. The method isused to analyze the qualitative descriptive data retrieval technique that is by observation,questionnaires and interviews. Based on the research, it was concluded that in general,respondents had an interest and reading different reason for understanding the activity ofreading, awareness of the benefits of reading, use of time reading and other types of readingpassages also vary. In general, respondents do activities reads as there are elements ofsatisfaction and interest in reading activities, students want to do so.Keywords: Interest In Reading and College student